Visualization and Interpretation of PM10 Monitoring Data Related to Causes of Haze Episodes in Northern Thailand - Sirapong Sooktawee; Usa Humphries; Aduldech Patpai; Rungrawee Kongsong; Suteera Boonyapitak; Nirun Piemyai (Applied Environmental Research, 2015)
Monitoring of ambient air quality yields data typically presented as time series plots, tables of summarized statistical values, or other representations. This paper presents an alternative way to visualizing air quality monitoring data by presenting concentrations in the form of a calendar, offering a familiar way for reader to identify air quality trends on various time scales (daily, weekly, or monthly). One of the major air pollution problems in the northern part of Thailand is haze, which is related to the concentration of airborne particulates less than 10 microns in size (PM10). This paper presents calendars of PM10 concentrations monitored by the Pollution Control Department across northern Thailand. Hourly mean PM10 concentrations monitored at 13 stations were used to construct PM10 concentration calendars for each station. Haze episodes are clearly identifiable in the visualization; the calendar also allows easy comparison of PM10 levels between years. We also observed the absence of any haze episodes in 2011, and propose possible related factors.